PENANAMAN NILAI-NILAI MULTIKULTURALISME DALAM KURIKULUM PENDIDIKAN ISLAM:: SEBUAH UPAYA KONTRA NARASI RADIKALISME - Mulawarman Hannase; Fatwa Arifah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
This article examines how to implement the values of multiculturalism in the Islamic education curriculum as an attempt to counter narrative of radicalism in various educational institutions. This study is regardly important due to currently in the development of educational curriculum, the issue of intolerance and split religious understanding has come to the attention of the government as well as society of Indonesia. This study is a qualitative by using multicuralism theory of James A. Bank's. The study confirm that multiculturalism-based learning which contains of values of togetherness, humanity, tolerance, culture and local wisdom should be adopted as an alternative to counter radical narrative in the different educational institutions.